FORMULATION AND EVALUATION OF SHEET MASK FROM RED RICE (Oryza nivara) EXTRACT - Hari Kusumawati, Anggun; Sri Gunarti, Neni; Ridwanuloh, Dadan; Supriadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
Sheet mask can moisturize the skin because of the sheet mask contained essence in the can help to moisturize the skin on the face, sheet mask is also very suitable for those who have dry skin. Sheet Mask from Red Rice (Oryza nivara) extract is to help skin care to rejuvenate facial skin from sun exposure after a day of activities. Facial masks have the ability to cleanse the skin to a deeper layer that cannot be reached with regular washing. Masks are useful for tightening, improving blood circulation, smoothing the skin, moisturizing the skin and refreshing the skin. Extraction is done by cold or maceration method. The extraction result from 4,300 kg of Red Rice Simplicia (Oryza nivara), obtained by the ethanol extract of Red Rice (Oryza nivara) as much as 73.85 g., With a yield of 1.7174%. Phytochemical screening is carried out which includes the identity of extracts, organoleptic extracts and phytochemical screening.Based on the results of testing the physical properties of sheet mask preparations, which consist of organoleptics, pH testing, viscosity testing, homogeneity testing of each formula, the essense sheet mask preparations are getting thicker viscosity when Carbopol concentration is added. The pH value of brown rice sheet mask preparations on all formulations by showing skin pH is around 4.5 - 6.5. The higher the concentration of the Carbopol gelling agent the higher the viscosity value. As in the table with formulation (F1) the viscosity value is higher than the viscosity value of the formulation (F2) and (F3). Based on the analysis that has been done on the preparation of red rice essense sheet mask (Oryza nivara) it can be concluded that all formulations produce good physical properties.